On skin microrelief and the emergence of expression micro-wrinkles. Issue 8 (10th January 2018) - Limbert, G.; Kuhl, E.
Abstract : Human skin microrelief conditions the pattern of expression micro-wrinkles at moderate stiffness ratios between stratum corneum layer and underlying substrate. Abstract : Over the course of a life time, as a result of adaptive mechanobiological processes ( e.g. ageing), or the action of external physical factors such as mechanical loading, the human skin is subjected to, and hosts complex biophysical processes. These phenomena typically operate through a complex interplay, that, ultimately, is responsible for the evolutive geometrical characteristics of the skin surface. Wrinkles are a manifestation of these effects. Although numerous theoretical models of wrinkles arising in multi-layered structures have been proposed, they typically apply to idealised geometries. In the case of skin, which can be viewed as a geometrically complex multi-layer assembly, it is pertinent to question whether the natural skin microrelief could play a significant role in conditioning the characteristics of compression-induced micro-wrinkles by acting as an array of geometrical imperfections. Here, we explore this question through the development of an anatomically-based finite strain parametric finite element model of the skin, represented as a stratum corneum layer on top of a thicker and softer substrate. Our study suggests that skin microrelief could be the dominant factor conditioning micro-wrinkle characteristics for moderate elastic modulus ratios between the two layers. Beyond stiffness ratios of 100, other factors tend to overwrite the effects of skin microrelief. Such stiffness ratio fluctuations can be induced by changes in relative humidity or particular skin conditions and can therefore have important implications for skin tribology.